Operations Research; Statistical Decision Theory: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
The paper analyzes two regression methods for a set of data relative to the absolute values, respectively their variation indices. A number of conclusions are drawn regarding the closest forecast to reality.